Answer:
The solutions to the quadratic equations are:
[tex]x=\sqrt{13}+3,\:x=-\sqrt{13}+3[/tex]
Step-by-step explanation:
Given the function
[tex]y\:=\:x^2\:-\:6x\:-\:4[/tex]
substitute y = 0 in the equation to determine the zeros
[tex]0\:=\:x^2\:-\:6x\:-\:4[/tex]
Switch sides
[tex]x^2-6x-4=0[/tex]
Add 4 to both sides
[tex]x^2-6x-4+4=0+4[/tex]
Simplify
[tex]x^2-6x=4[/tex]
Rewrite in the form (x+a)² = b
But, in order to rewrite in the form x²+2ax+a²
Solve for 'a'
2ax = -6x
a = -3
so add a² = (-3)² to both sides
[tex]x^2-6x+\left(-3\right)^2=4+\left(-3\right)^2[/tex]
[tex]x^2-6x+\left(-3\right)^2=13[/tex]
Apply perfect square formula: (a-b)² = a²-2ab+b²
[tex]\left(x-3\right)^2=13[/tex]
[tex]\mathrm{For\:}f^2\left(x\right)=a\mathrm{\:the\:solutions\:are\:}f\left(x\right)=\sqrt{a},\:-\sqrt{a}[/tex]
solve
[tex]x-3=\sqrt{13}[/tex]
Add 3 to both sides
[tex]x-3+3=\sqrt{13}+3[/tex]
Simplify
[tex]x=\sqrt{13}+3[/tex]
now solving
[tex]x-3=-\sqrt{13}[/tex]
Add 3 to both sides
[tex]x-3+3=-\sqrt{13}+3[/tex]
Simplify
[tex]x=-\sqrt{13}+3[/tex]
Thus, the solutions to the quadratic equations are:
[tex]x=\sqrt{13}+3,\:x=-\sqrt{13}+3[/tex]